(3GdYbO GdaQjO ddedc GdSYjOs - (3CHh SGde GdfUjHj , eMeO Hf WdMg Hf eMeO Hf GdMSf GdbQTj, ceGd GdOjf CHh SGde,J (B652 (3g` s ((3eOjfI UaO s)
(3ChdgG (B:s
(3hHYO, aEf bde GdbOQ LQi aj GdbOe HJCjjO Gddg JYGdi hESYGOg def GNJUg ef edhc GdOfjG s
(3BNQgG (B:s
(3abO fbd Yf GdfHj Udi Gddg Ydjg hSde Cfg bGd(B: (3hdjcf gPG GdOYGA GdeSJLGH Ef TGA Gddg dgPG GdcJGH NJGe cdeGJg fLR gPG GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B175s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B42 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1152s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs